Fractionation of a phenolic compound from water spinach (Ipomoea aquatica) herbs as anti-dandruff against Malassezia sp. - Meta Damaharyuningtyas; Kintoko Kintoko; Endang Darmawan (Universitas Ahmad Dahlan, 2022)
Dandruff is a scalp disorder caused by a fungus (Malassezia sp.). Water spinach (Ipomoea aquatica) contains phenolic compounds which has antifungal activity. The purpose of this research is to know the active fraction of Ipomoea aquatica herb which has antidandruff activity to against Malassezia sp. The study used true experimental design to antidandruff activity test. Fractionation used column chromatography which stationary phase with silica gel 60 powder and mobile phase with chloroform/methanol/acetyl acetate (8/2/0,1 v/v/v). In vitro antidandruff activity based on minimum inhibitory consentration (MIC) and minimum antifungal consentration (MFC) against Malassezia sp. of human dandruff isolate. The average of MIC and MFC among groups compared used Friedman test test (p≤ 0,05). The fraction 7 of water spinach (Ipomoea aquatica) herb have antidandruff activity against Malassezia sp. (MIC 125 µg/mL and MFC 250 µg/mL). Based on the results, fraction of water spinach (Ipomoea aquatica) herb have antidandruff activity against Malassezia sp. identified as phenolic compound.